Experimental aerothermal characterization of surface air-cooled oil coolers for turbofan engines. (July 2022) - Broatch, A.; Olmeda, P.; García-Tíscar, J.; Felgueroso, A.; Chávez-Modena, M.; González, L.M.; Gelain, M.; Couilleaux, A.
Highlights: An experimental methodology for reduced-scale testing of SACOCs is proposed. A facility has been commissioned reproducing turbofan bypass flow conditions. Three heat exchanger geometries have been aero-thermally characterized. Impact of the SACOC on the bypass duct flow field has been assessed. A proposed optimized fin geometry has demonstrated significant improvements. Abstract: Thermal management is a major challenge for new generation turbofan aero-engines. One of the most promising heat exchangers are the so-called surface air-cooled oil coolers (SACOCs). In this study, an experimental methodology is proposed and implemented in order to characterize SACOCs mounted in turbofan bypass ducts. Three different SACOC geometries have been characterized under the same nominal operating point, while the actual velocity profile in the bypass was reproduced by means of a distortion screen upstream the test section. The heat exchangers were mounted in counterflow configuration and feature the same fin geometry in the oil side. The three prototypes varied only in the air side, being the first a baseline flat plate, the second a SACOC with standard trapezoidal fins and the third featuring optimized fins designed to reduce the pressure drop. Aerothermal results demonstrated that the effect of the SACOC on the bypass flow was confined to a region about the same height and width of the finned area, avoiding the need of reproducing the whole bypass duct. However, for this reduced-height experimental approach to be valid, we show that the velocity profile needs to be rearranged to match the specific section of the whole bypass. We also demonstrate how the optimized fin geometry achieved a 10% lower friction factor than the standard one at nominal flow conditions while increasing the overall heat transfer coefficient by 5.2%.